Constructions of colonialism : perspectives on Eliza Fraser's shipwreck - McNiven, Ian J.; Russell, Lynette; Schaffer, Kay, 1945- (Leicester University Press, 1998)
One of the most famous shipwreck sagas of the 19th century took place on the tropical coast of north-east Australia. In 1836 the Stirling Castle was wrecked off the Queensland coast and many of the crew, together with the captain''s wife, Eliza Fraser, were marooned on Fraser Island. Early sensationalized accounts represent Mrs Fraser as an innocent white victim of colonialism and her Aboriginal captors as barbarous savages. These ""first contact"" narratives of the white woman and her Aboriginal ""captors"" impacted significantly on England and the politics of Empire at an early stage.